2018
DOI: 10.1111/imig.12533
|View full text |Cite
|
Sign up to set email alerts
|

Implementing and Rethinking the European Union's Asylum Legislation: The Asylum Procedures Directive

Abstract: The Asylum Procedures Directive, which was put in place in the context of the Common European Asylum System, is expected to both harmonise the asylum procedures in the European Union and to safeguard applicants’ rights. This article explores various steps in the implementation of the directive, starting with transnational negotiations which aim to influence domestic asylum policies. Focusing on asylum systems in Germany and Sweden, the article shows that the way decision makers implement the directive is shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…A recent empirical study into the implementation of the Asylum Procedures Directive, for instance, found that it 'is compatible with different, sometimes even contrasting properties of domestic asylum policies', and that 'the risk of failing common standards and the principles of international refugee law is… not only a matter of implementation, but is already inherent in the Directive's design'. 88 The shortcomings identified were the great deal of flexibility afforded to MS in interpreting and implementing the Directive and the ambiguity of its language, including inherent contradictions of its underlying objectives (e.g. claiming to strengthen procedural rights of asylum-seekers but introducing compulsory accelerated asylum procedures with limited procedural guarantees).…”
Section: Critical Analysismentioning
confidence: 99%
“…A recent empirical study into the implementation of the Asylum Procedures Directive, for instance, found that it 'is compatible with different, sometimes even contrasting properties of domestic asylum policies', and that 'the risk of failing common standards and the principles of international refugee law is… not only a matter of implementation, but is already inherent in the Directive's design'. 88 The shortcomings identified were the great deal of flexibility afforded to MS in interpreting and implementing the Directive and the ambiguity of its language, including inherent contradictions of its underlying objectives (e.g. claiming to strengthen procedural rights of asylum-seekers but introducing compulsory accelerated asylum procedures with limited procedural guarantees).…”
Section: Critical Analysismentioning
confidence: 99%
“…Collaboration with civil society actors is very important for EU institutions (Ruzza, 2015); and several well-established organizations are present and active on LGBTI+ and migration issues. The role of these actors in compensating for the restrictive vision carried by other EU actors has been studied in the case of the CEAS (Schittenhelm, 2019).…”
Section: Failure To Build Common Advocacy At An Eu Levelmentioning
confidence: 99%
“…However, with the Treaty of Amsterdam in 1997 the EU gained the ability to create binding rules concerning asylum, laying the groundwork for subsequent harmonization of EU asylum policy (Hatton, 2005). Although asylum is defined under UN statute and the Tampere agreement and Dublin Regulations provide additional EU-specific procedures and oversight to the asylum process, EU efforts to harmonize asylum policy have not produced equal outcomes (Hatton, 2005; Schittenhelm, 2019; Trauner, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%